Chiral Separation of Indapamide Enantiomers by Capillary Electrophoresis - Amelia Tero-Vescan; Gabriel Hancu; Mihaela Oroian; Anca Cârje (Tabriz University of Medical Sciences, 2014)
Purpose: Indapamide is probably the most frequently prescribed diuretic drug, generally being used for the treatment of hypertension. It contains a chiral center in its molecule; is marketed as a racemic mixture; but there are rather few studies regarding the pharmacokinetic and the pharmacological effect differences of the two enantiomers. Our aim was the development of a simple, rapid and precise analytical procedure for the chiral separation of indapamide enantiomers. Methods: In this study capillary zone electrophoresis was used for the enantiomeric separation of indapamide using a systematic screening approach involving different native and derivatized; neutral and charged cyclodextrines as chiral selectors. The effects of pH value and composition of the background electrolyte, capillary temperature, running voltage and injection parameters have been investigated. Results: After preliminary analysis a charged derivatized CD, sulfobuthyl ether- β-CD, proved to be the optimum chiral selector for the enantioseparation. Using a buffer solution containing 25 mM disodium hydrogenophosphate - 25 mM sodium didydrogenophosphate and 5 mM sulfobuthyl ether- β-CD as chiral selector at a pH - 7, a voltage of + 25 kV, temperature 15°C and UV detection at 242 nm, we succeeded in the separation of the two enantiomers in approximately 6 minutes, with a resolution of 4.30 and a separation factor of 1.08. Conclusion: Capillary zone electrophoresis using cyclodextrines as chiral selectors proved to be a suitable method for the enantioseparation of indapamide. Our method is rapid, specific, reliable, and cost-effective and can be proposed for laboratories performing indapamide routine analysis.